The antecedents of fraud behavior: A finding from Indonesia - Syofyan, Efrizal; Pradini, Dewi; Tri Kurniawati, Tri Kurniawati (2017)
Corruption is an unethical behavior that harms society and the state.The perpetrators of corruption perform their actions for various reasons and motives.This paper is aimed to analyze the influence of pressure, opportunity and rationalization on corruption behavior of corruption prisoners in West Sumatera.We hypothesize that these three variables have a significant effect on corruption in West Sumatera. This research used a quantitative research with correlational approach.This article used multiple regression analysis to analyze the relationship between the independent variable (pressure, opportunity and rationalization) on the dependent variables of corruption.The pressure has no sginificant effect on corruption behaviour of inmates in Prison of Muaro Padang.Opportunities have a significant and positive effect on corruption. Rationalization also has a significant and positive effect on corruption.There is several research regarding to corruption perpetrator in many countries.But research on corruption perpetrators in West Sumatera is still limited. Furthermore, West Sumatera is a province which occupied by Minangkabau people that famous for their religious life.